Non‐genetic factors associated with ACE‐inhibitor and angiotensin receptor blocker‐induced angioedema - Diana Dubrall; Nora L. Branding; Carina M. Mathey; Anna M. Weber; Michael Steffens; Maike Below; Matthias Schmid; Bettina Wedi; Dorothea Wieczorek; Philipp M. Amann; Harald Löffler; Lukas Koch; et al. (Clinical and Translational Allergy)
Abstract Background Angioedema (AE) rarely occurs as a potentially life‐threatening adverse drug reaction (ADR) to angiotensin‐converting enzyme inhibitors (ACEi) or angiotensin receptor blockers (ARB). The aim of the present study was to investigate non‐genetic association factors with ACEi‐/ARB‐induced angioedema in the European ADR database EudraVigilance and the database of the vARIANCE study. Methods The cohort of the vARIANCE study comprised 114 patients who suffered from ACEi‐ or ARB‐induced angioedema. In addition, 171 angioedema reports and 4650 reports on other ADRs of ACEi/ARB were identified in the ADR database EudraVigilance with the latter serving as a reference group. Odds ratios were calculated and a logistic regression analysis was performed using angioedema versus reference reports. Results Increased age, smoking, allergies and a history of previous angioedema were identified as associated factors for ACEi‐/ARB‐induced angioedema. In most patients, the swelling affected the face, lips and tongue. In the vARIANCE study, about 70% of angioedema occurred after 1 year of treatment. For one in two patients in the vARIANCE study (84.2% with ACEi treatment) and one in three patients from the EudraVigilance reports (59.6% with ARB treatment), the angioedema resulted in hospitalization. Conclusions We found small to moderate associations with certain individual patient‐related factors in this pharmaco‐epidemiological study. As a future perspective, combining non‐genetic association factors with corresponding genetic data might provide an option to compose stronger and individual risk scores.